TRP channel pores and local calcium signals. (September 2017) - Mulier, Marie; Vriens, Joris; Voets, Thomas
Graphical abstract: Highlights: TRP channels display variable selectivity for calcium ions. Differences in the pore structure underlie differences in calcium selectivity. Opening of single or few TRP channels can evoke highly localized calcium signals. Abstract: Calcium signals control a plethora of essential cellular functions ranging from secretion and contraction to gene expression and sensory signaling cascades. An essential part of intracellular calcium signals originates from the transmembrane flux of calcium ions, which is mainly mediated through different calcium-permeable cation channels with variable calcium selectivity. Opening of individual calcium permeable channels induces a local cytosolic calcium rise that can be highly restricted in time and space. Here, we provide a short overview of the current knowledge about calcium permeation and localized calcium signals in transient receptor potential (TRP) channels. We also present a brief survey of some fundamental theoretical aspects of the local calcium signals generated upon opening of single calcium-permeable channels, and compare theoretical predictions with published experimental data on TRP channel-mediated local calcium signals.